La tradizione manoscritta dell "ars dictaminis" nell'Italia medievale "Mise en page" e "mise en texte" - Bischetti, Sara (Toscana Bilingue. Storia sociale della traduzione medievale / Bilingualism in Medieval Tuscany, 2022)
This volume is dedicated to the study of medieval ars dictaminis. Analyzing several manuscript witnesses, it sheds light on the historical contextualization of the phenomenon and examines the close relationship between ars dictaminis and the political and social system of that time.